Performance-Based Building: Architecture of an Integrated Model at Conceptual and Practical Dimensions - arslan, serkan (Advances in Social Sciences Research Journal, 2018)
ABSTRACT Traditional building production process is a multi-phased and multi-stakeholder process which is fragmented too much in many aspects. Naturally, the process of production which has already difficulties due to reasons such as disconnections among the organizations which is included in the process during transitions between phases and which undertake various responsibilities in each phase, missing project documentation, conflicts of interests of the stakeholders and similar reasons becomes even more complicated and the output of this process is also often problematic. While the clients, who makes the basic decisions, forms the product and the process to maximize their profit, the end user especially in underdeveloped countries is victimized due to the inadequacy of legal regulations, lack of information on the standard performance values which the product has to provide, weakness of the mechanisms to protect the interests of the community in design and construction processes to overcome these deficiencies in addition to reluctance to meet the cost of individually needed expert support and what’s more, losses occur at national and global scales, resources are wasted and problems as to sustainable development arise. The traditional construction process which while trying to minimize the first investment cost, causes increasing life cycle cost to high levels stands out as a structure for which particularly developing countries have to rethink of and develop alternative models. At this point, Performance-Based Building phenomena seems to draw more attention as a solution. This study aims to discuss the above stated approach as well as structure and tools which support this approach with all of its dimensions at conceptual levels and define the architecture of the model required to transfer them to practice at conceptual and practical dimensions.